Visual function scale for identification of infants with low respiratory compliance - Eimei Harada; Masahiro Kinoshita; Sachiko Iwata; Mamoru Saikusa; Kennosuke Tsuda; Ryota Shindou; Takeshi Sahashi; Shin Kato; Yasumasa Yamada; Shinji Saitoh; Osuke Iwata (Pediatrics and Neonatology, 2019)
Aim: Precise estimation of respiratory function is essential to optimise neonatal respiratory care. However, current clinical scores have not been validated with quantitative measures of respiratory function. The aim of this study was to develop a physiological scoring system to predict low respiratory dynamic compliance of <0.6 ml/cmH2O/kg. Methods: Forty-four newborn infants were studied before (dynamic compliance) and shortly after scheduled extubation (physiological signs). A novel scoring system was developed based on the association between physiological signs and dynamic compliance. Results: The respiratory rate was identified as the primary independent variable for dynamic compliance in the univariate analysis. The prediction score for low dynamic compliance comprised the presence of nasal flaring, see-saw respiration, suprasternal/intercostal retraction, and the respiratory rate ranks (0–3). The area under the receiver–operating characteristics curve of the composite score had discriminatory capability of 0.86 (95% confidence interval: 0.75–0.97) to predict low dynamic compliance with the optimal cut-off value of ≥3 (sensitivity, 0.882; specificity, 0.667). Conclusion: Our novel scoring system might help predict newborn infants with low dynamic compliance, who may require escalation of respiratory support, or transfer to higher level units. Key Words: Lung compliance, Newborn infant, Respiratory failure, Resuscitation